New size number and the fracture state of concrete structure - Tu, V. Tran (Vietnam Journal of Mechanics, 1996)
A new size number describing the fracture state of concrete structures is developed in which the structural size and the main fracture properties of concrete are dealt with. The relation between the fracture state of concrete beams loaded in bending and the newly proposed size number is presented graphically. The shape of the stress - crack curve, which is a typical property of most quasi-brittle composites like concrete, is found to be an important factor in determining the size number together with the fracture energy, the elastic modulus and the ultimate tensile strength of materials. The influence of 'the structural size on the fracture state is also graphically presented.